KAJIAN ETHNICHEMISTRY DALAM PEMBELAJARAN KIMIA MELALUI INTEGRASI BUDAYA MENYIRIH PADA MATERI GUGUS FUNGSI DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK - Ika Kartikasari; Bambang Hariyadi; Zurweni Zurweni; Haryanto (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to examine the application of the ethnochemistry approach in chemistry learning through the integration of betel chewing culture in functional group material using a scientific approach. The betel chewing culture involving materials such as betel leaves (Piper betle), areca nut (Areca catechu), and betel lime (calcium hydroxide) is known to contain various active chemical compounds, including alkaloids, phenols, esters, and alcohols. The scientific approach allows students to observe, ask, try, reason, and communicate the results of the analysis of these materials, so that they can understand the concept of functional groups in the context of local culture. This study uses a descriptive qualitative method with a literature study approach and participatory observation of the practice of betel chewing culture in the community. The results of the study show that the integration of local culture in chemistry learning can improve students' conceptual understanding, learning interest, and cultural awareness. The ethnochemistry approach has proven effective in creating contextual, meaningful, and relevant learning to students' daily lives. Therefore, the application of a local culture-based learning model through a scientific approach is recommended as an innovative alternative in chemistry learning. Keywords: Ethnichemistry, betel chewing culture, scientific approach, functional groups, contextual chemistry learning.